GAMBARAN KOMORBID PASIEN HEMODIALISA - Utami, Maria Putri Sari; Rosa, Elsye Maria; Khoiriyati, Azizzah (STRADA : Jurnal Ilmiah Kesehatan, 2017)
Mostly patient with ESRD choosed Renal replacement therapy hemodialysis. on the other hand. Although hemodialysis therapy is the most preferred, not all toxic can be removed from the body. It was able to bring comorbid in hemodialysis patients. Comorbidity was one of the factors that affected life in patients with hemodialysis. This study evaluated comorbidity in hemodialysis patients. 79 samples on hemodialysis unit in PKU Muhammadiyah Yogyakarta hospital were collected during March to May 2016. Descriptive analytic cross sectioanal study was used and comorbidity data’s obtained from medical records of patients.Most comorbid in hemodialysis patients are hypertension, followed by diabetes mellitus, and heart disease. Hemodialysis patients have comorbid more than one. Most comorbid in hemodialysis patients are hypertension, followed by diabetes mellitus, and heart disease. Comorbid in hemodialysis patients need a special attention. Health care practitioners should not only focus on hemodialysis, but also the patient’s comorbid.